The Effect of Internal Control of Goods and Services Procurement and Budget Planning Quality on Budget User Efficiency at Siti Fatimah Regional General Hospital of South Sumatra Province - Zulkarnain; Yancik Syafitri; Amanda Oktariyani (International Journal of Business and Quality Research, 2026)
This study aims to examine the effect of internal control of goods and services procurement and budget planning quality on budget user efficiency at Siti Fatimah Regional General Hospital, South Sumatra Province. This study employed a quantitative approach using a questionnaire survey distributed to employees involved in hospital management and financial activities. The population consisted of 1,209 employees, with 73 respondents selected through a purposive sampling technique based on predetermined criteria. The data were analyzed using multiple linear regression with the assistance of SPSS. The results indicate that internal control of goods and services procurement and budget planning quality significantly influence budget user efficiency. The partial test results show that both internal control of goods and services procurement and budget planning quality have a significant effect on budget user efficiency. These findings emphasize that effective procurement control and accurate budget planning are important factors in improving the efficiency of budget utilization in public healthcare institutions. This study provides practical implications for hospital management in strengthening internal control mechanisms and improving budget planning processes to achieve more effective and accountable financial management.